Formation and Evolution of State-Sponsored Nation Building in the UAE - Hojjat Kazemi; Mohammad Mahboubi (رهیافتهای سیاسی و بین المللی)
The founding of the United Arab Emirates in the early 1970’s was the product of a political will to unite a set of tribal communities in which their dominant identity was a combination of tribal and Islamic identity. The conversion of the emerging country from a disintegrated collection into a cohesive political unit required the creation of elements that constructs national identity and its internalization and generalization as an identity beyond tribal belongings and below national belongings that binds citizens together and gives them a sense of nationhood. Given to the chronological precedence of the state establishment over the nation, and to the centrality of political institutions and elites, the nation building experience in the UAE is an obvious sample of a nation building pattern that can be called "state-sponsored nation building". State-sponsored nation building as a form of nation building in modern age is a process "from above" during which the state and its institutions try to shape elements and components of national identity and to develop it among their citizens, through the design and implementation of targeted projects; and thus create a new basis for social belonging. The present article attempts to examine the dimensions, elements, and technics of such a process in the United Arab Emirates at the Mohammed bin Zayed Al Nahyan era. Based on the "modernist" theorists’ studies about nationalism, this article categorizes and studies the technics of nation building under four axes: a. tradition-constructing; b. history-constructing; c. symbol-constructing; d. alter-constructing.